INTRASPECIFIC VARIATION IN AETOSAUROIDES SCAGLIAI CASAMIQUELA (ARCHOSAURIA: AETOSAURIA) FROM THE UPPER TRIASSIC OF ARGENTINA AND BRAZIL: AN EXAMPLE OF SEXUAL DIMORPHISM? (Ameghiniana, 2015)
Aetosaurs are a group of quadrupedal, armoured pseudosuchian archosaurs from the Upper Triassic. They are characterized by dorsal and ventral carapaces, and appendicular osteoderms, all of them ornamented. Aetosaurs have been proposed as index fossils largely based on the distinctiveness of some osteoderms. Therefore, it is important to understand the intraspecific variation of these elements in the clade. In the present contribution, we describe three types of ornamentation on the medial area of paramedian osteoderms in the dorsal armour of Aetosauroides scagliai Casamiquela: the “radial pattern” the “anastomosing pattern”; and an “intermediate” or “transitional pattern”, that is an intermediate between “radial” and “anastomosing” patterns. The articulated dorsal armour preserved in specimens PVL 2059 and PVL 2073 possesses osteoderms carrying all three patterns of ornamentation, but they differ by the position of each type of osteoderm on the carapace. Recent studies on histological thin-sections of osteoderms of A. scagliai reveal the absence of osteoderm tissue remodeling, allowing the estimation of age by counting LAGs (lines of arrested growth). PVL 2073 is slightly shorter (~10% longer centra) but also ontogenetically younger (5 LAGs) than PVL 2059 (10 LAGs; slightly wider osteoderms). Combining this information and comparing it with that of living crocodiles (where male specimens typically are relatively larger than females of the same age), we conclude that the intraspecific variation observed in A. scagliai is compatible with the hypothesis of sexual dimorphism. These results suggest the need to explore the sources of intraspecific variation in aetosaurs. Resumen. VARIACIÓN INTRAESPECÍFICA EN AETOSAUROIDES SCAGLIAI CASAMIQUELA (ARCHOSAURIA: AETOSAURIA) DEL TRIÁSICO SUPERIOR DE ARGENTINA Y BRASIL: UN EJEMPLO DE DIMORFISMO SEXUAL?. Los aetosaurios son un grupo de arcosaurios pseudosuquios cuadrúpedos y acorazados del Triásico superior. Se Caracterizan por tener una coraza dorsal, una ventral, y osteodermos apendiculares, todos ornamentados. Los aetosaurios fueron propuestos como fósiles guía con base en características distintivas en algunos osteodermos. Por lo tanto, es importante comprender las variaciones intraespecíficas de estos elementos dentro del clado. En la presente contribución, se describen tres tipos de ornamentación en el área medial de los osteodermos paramediales de la coraza dorsal de Aetosauroides scagliai Casamiquela 1960: un “patrón radial”; un “patrón anastomosado”; y uno “intermedio” o “patrón transicional” entre el radial y el anastomosado. Las corazas articuladas de los especímenes PVL 2059 y PVL 2073 muestran los tres tipos de ornamentación, pero con una variación en la posición dentro de la coraza de los osteodermos con estas ornamentaciones. Recientes estudios paleohistológicos en osteodermos de A. scagliai muestran la ausencia de remodelación en los tejidos de los mismos permitiendo la estimación de edad mediante el conteo de LACs (líneas anuales de crecimiento). El PVL 2073 es ligeramente más corto (~10% en los centros) pero también más joven ontogenéticamente (5 LACs) que el PVL 2059 (10 LACs; y osteodermos ligeramente más anchos). Combinando esta información y comparándola con los cocodrilos actuales (donde los machos son generalmente más grandes que las hembras para una misma edad), concluimos que la variación intraespecífica observada en A. scagliai es compatible con la hipótesis de un dimorfismo sexual. Estos resultados evidencian la necesidad de estudiar las variaciones intraespecíficas en aetosaurios.